The Effect of Implementing The MTBK 4C Skills-Based Microsoft Teams Application and Independence on Student Learning Outcomes in Broad-Based Network Technology Subjects - Hidayati Hidayati; Taali Taali; Ambiyar Ambiyar; Resmi Darni (STAI Miftahul Ula Nganjuk, 2022)
The problem in this study is that learning methods are still poorly developed and are still teacher center in nature so that there is a lack of independence and curiosity about learning materials that cause suboptimal learning outcomes. This study aims to determine the influence of the use of MTBK4C and student independence on learning outcomes in broad-based network technology subjects. This study used a quasi-experimental type of research. This study used a 2x2 factorial design (factorial design) modifying from an experimental true design, namely by paying attention to the moderator variables that affect the treatment (independent variable) of learning outcomes (dependent variable). The population in this study was all students of class XI TJKT SMK Negeri 2 Padang. The results obtained from this study are seen from the hypothesis: 1) the first hypothesis of learning outcomes using the MTBK4C learning application is better than conventional learning with a value of 0.0085 < 0.025, 2) Learning outcomes of Broad-Based Network Technology students who have high independence are higher than the learning outcomes of students who have low independence in terms of value 0.000 < 0.005, 3) Learning outcomes of Broad-Based Network Technology students who use the MTBK4C application with high independence are better than conventional learning with high independence assessed based on the results of the Tuckey test with a high learning independence score having an average learning outcome score of 82.46 > learning proficiency high has an average score of 75.33, 4)Learning outcomes of Broad-Based Network Technology students who use the MTBK4C application with low independence are better than conventional learning with low independence assessed based on the results of the Tuckey test with low learning independence scores have a learning outcomes score an average of 71.26 > low learning proficiency had an average score of 62, and 5) There was a significant interaction between the use of MTBK4C learning media and the independence of learner learning in influencing student learning outcomes in broad-based Network Technology subjects based on a probability value of 0.014 < 0.05 . Based on the results of this study, it can be concluded that itcan influence the application of the MTBK4C application and independence on student learning outcomes in improving student activities, independence and learning outcomes in the subject of Broad-Based Network Technology.